Imaging of the adrenal gland lesions - Herr,Keith (2014)
With the steep increase in the use of cross-sectional imaging in recent years, the incidentally detected adrenal lesion, or "incidentaloma", has become an increasingly common diagnostic problem for the radiologist, and a need for an approach to classifying these lesions as benign, malignant or indeterminate with imaging has spurred an explosion of research. While most incidentalomas represent benign disease, typically an adenoma, the possibility of malignant involvement of the adrenal gland necessitates a reliance on imaging to inform management decisions. In this article, we review the literature on adrenal gland imaging, with particular emphasis on computed tomography, magnetic resonance imaging, and photon-emission tomography, and discuss how these findings relate to clinical practice. Emerging technologies, such as contrast-enhanced ultrasonography, dual-energy computed tomography, and magnetic resonance spectroscopic imaging will also be briefly addressed.